Research on differences set pairs and periodic complementary binary sequence pairs - JIA Yan-guo; XU Cheng-qian (Tongxin xuebao)
The differences set pairs were studied and some constructions of differences set pairs were put forward.A con-struction of periodic complementary binary sequence pairs based on differences set pairs was put forward.It can expedi-ently find plentiful periodic complementary binary sequence pairs.